Le moment du mémoire : un moment formatif avec la pratique du journal de recherche - Laurence Zigliara; Anne Olivier; Séverine Parayre; Augustin Mutuale (Université de Provence, 2018)
ISP-Faculty of the Catholic Institute of Paris introduced the practice of the research diary since three years in order to facilitate the writing of the Master dissertation and the beginning of the research for the students teachers. We wanted to analyze if this practice and tool were "significant" and "facilitators" for their users. Several semi-directive interviews were led to identify advantages and inconveniences, uses and reuses of this practice and this tool. A crossed analysis of interviews was brought to determining elements: at first the difficulty shared at the beginning of the writing process. Once this apprehension is overcome the practice is integrated and the tool used in a permanent way for construction and writing of dissertation. Indeed, the interviewed people revealed to better organize their ideas and their reflection, problematize their subject and managing to write their dissertation. Finally the research diary participates in the research student's identity and, on the long term, of the reflexive practitioner. Practice and tool can be integrated into professional life; with for consequence to transform and/or to develop it.